2019
DOI: 10.1103/physrevb.100.064304
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning determination of dynamical parameters: The Ising model case

Abstract: We train a set of Restricted Boltzmann Machines (RBMs) on one-and two-dimensional Ising spin configurations at various values of temperature, generated using Monte Carlo simulations. We validate the training procedure by monitoring several estimators, including measurements of the log-likelihood, with the corresponding partition functions estimated using annealed importance sampling. The effects of various choices of hyper-parameters on training the RBM are discussed in detail, with a generic prescription prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 14 publications
4
63
0
Order By: Relevance
“…In Figure 13 the plot for L = 150 indicates that the transition occurs right at the critical temperature. One can fit the points of the latent variable which behave linearly to a constant as a function of the temperature and can restrict that the collapse of the two states located at 1 and −1 occurs at T = 2.288 (21). This is in good agreement with the theoretical prediction.…”
Section: Results For the Anti-ferromagnetic Ising Modelsupporting
confidence: 75%
See 1 more Smart Citation
“…In Figure 13 the plot for L = 150 indicates that the transition occurs right at the critical temperature. One can fit the points of the latent variable which behave linearly to a constant as a function of the temperature and can restrict that the collapse of the two states located at 1 and −1 occurs at T = 2.288 (21). This is in good agreement with the theoretical prediction.…”
Section: Results For the Anti-ferromagnetic Ising Modelsupporting
confidence: 75%
“…Recent advances in the implementation of Artificial Intelligence (AI) for physical systems, especially, on those which can be formulated on a lattice, appear to be suitable for observing the corresponding underlying phase structure [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. So far methods such as the Principal Component Analysis (PCA) [6,10,12,18,19], Supervised Machine Learning (ML) [2,15,20], Restricted Boltzmann Machines (RBMs) [21,22], as well as autoencoders [6,13] appear to successfully identify different phase regions of classical statistical systems, such as the 2-dimensional (2D) Ising model that describes the (anti)ferromagneticparamagnetic transition. These techniques were also applied on quantum statistical systems, such as the Hubbard model [4] that describes the transition between conducting and insulating systems.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, tools from Statistical Physics have been applied to analyze the learning ability of RBMs (Decelle et al , 2018; Huang, 2017b), characterizing the sparsity of the weights, the effective temperature, the non-linearities in the activation functions of hidden units, and the adaptation of fields maintaining the activity in the visible layer (Tubiana and Monasson, 2017). Spin glass theory motivated a deterministic framework for the training, evaluation, and use of RBMs (Tramel et al , 2017); it was demonstrated that the training process in RBMs itself exhibits phase transitions (Barra et al , 2016, 2017); learning in RBMs was studied in the context of equilibrium (Cossu et al , 2018; Funai and Giataganas, 2018) and nonequilibrium (Salazar, 2017) thermodynamics, and spectral dynamics (Decelle et al , 2017); mean-field theory found application in analyzing DBMs (Huang, 2017a). Another interesting direction of research is the use of generative models to improve Monte Carlo algorithms (Cristoforetti et al , 2017; Nagai et al , 2017; Tanaka and Tomiya, 2017b; Wang, 2017).…”
Section: Generative Models In Physicsmentioning
confidence: 99%
“…ML models are able to automatically capture statistical characteristics by identifying and learning hidden patterns in data (Pathak et al 2018), making them ideally suited to detecting warning signals. Indeed, ML has been used to classify phases of matter, study phase behavior, detect phase transitions, and predict chaotic dynamics (Scandolo 2019, Van Nieuwenburg et al 2017, Canabarro et al 2019, Zhao and Fu 2019, Pathak et al 2018, whilst supervised learning algorithms such as artificial neural networks have been used to study second-order phase transitions, especially the Ising model (Morningstar and Melko 2017, Cossu et al 2019, Ni et al 2019, Giannetti et al 2019. However, thus far machine learning tools have not been used to classify the most common transitions seen in ecological, financial, and climatic systems -catastrophic (i.e., firstorder or discontinuous) and non-catastrophic (i.e., second-order or continuous) transitions (Martín et al 2015).…”
Section: Introductionmentioning
confidence: 99%